Treatment with betablockers is associated with higher grey-scale median in carotid plaques - Asciutto, Giuseppe (BioMed Central, 2014)
BACKGROUND: The presence of echolucent carotid plaques as defined by low ultrasound grey-scale median (GSM) is associated with a higher risk of stroke and myocardial infarction. Betablockers have shown possible anti-atherosclerotic effects. The aim of the present study was to determine if there is an association between carotid plaque GSM and treatment with betablockers. METHODS: The GSM of the carotid plaques of 350 patients who underwent carotid endarterectomy (CEA) for asymptomatic (n = 113) or symptomatic (n = 237) carotid disease was measured. Patients were divided in two groups based on the absence/presence of an on-going long-term (i.e. at least 6 months) oral treatment with betablockers at the time of CEA. RESULTS: The prevalence and type of preoperative neurological symptoms were similar in the two groups. Patients with betablockers had more frequently arterial hypertension (P < .0001), diabetes (P = .035) and a higher BMI (P = .0004), while patients without betablockers were most frequently smokers (P = .017). Patients with betablockers revealed to have higher GSM (37.79 ± 25 vs 32.61 ± 23.50 P = .036). Echogenic plaques (i.e. with GSM > 30) showed to be more frequent in patients with betablockers also after correction for age, gender, the occurrence of preoperative symptoms, diabetes, hypertension, smoking and statins use (P = .024). CONCLUSIONS: These results suggest the use of standardized ultrasound techniques as an important tool in evaluating the effect of anti-atherosclerotic medications and underline the need of.further prospective randomized studies on larger patient cohorts in order to confirm these results.